2004
DOI: 10.1063/1.1777416
|View full text |Cite
|
Sign up to set email alerts
|

Improved characteristics of organic light-emitting devicesby surface modification of nickel-doped indium tin oxide anode

Abstract: This letter presents the optoelectrical performance of an organic light-emitting diode (OLED) through the elevation of indium tin oxide (ITO) anode work function by Ni co-sputter surface doping and additional O2 plasma treatment. The turn-on voltage of OLED devices can be reduced by 2.3V for Ni atomic concentration greater than 1.8% and by 2.7V for the additional O2 plasma treatment. Devices with Ni(2.6%)-doped and O2 plasma treated ITO anodes perform the highest luminance efficiency (0.91lm∕W), three times la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…[13][14][15] Because the NiO x layer is a well-known p-type conductor with high work function, it is more desirable for hole injection into the organic layer than ITO.…”
Section: 14mentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15] Because the NiO x layer is a well-known p-type conductor with high work function, it is more desirable for hole injection into the organic layer than ITO.…”
Section: 14mentioning
confidence: 99%
“…For these reasons, several approaches have been employed to increase the work function of ITO, including wet treatment, 7,8 plasma treatment, 9,10 UV ozone treatment, 11 selfassembly monolayer coating treatment, 12 and Ni doping of ITO. 13,14 In particular, several groups have reported that Ni cosputtering with ITO or Ni doping on the surface region of an ITO can potentially enhance hole injection into OLEDs due to the effect of the p-type transparent conductive NiO x layer. [13][14][15] Because the NiO x layer is a well-known p-type conductor with high work function, it is more desirable for hole injection into the organic layer than ITO.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…And several kinds of approaches have been proposed to elevate the work function of ITO, such as using metal oxides with high work functions, inserting conducting polymers between ITO and organic material, and depositing metal-doped ITO layers on the ITO surface. [11][12][13] Iridium oxide ͑IrO x ͒ and ruthenium oxide ͑RuO x ͒ are transparent conducting oxides. The work functions of IrO x and RuO x ͑Ͼ5.0 eV͒ are higher than those of ITO ͑ϳ4.7 eV͒.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Several approaches for achieving an elevated ITO work function have been performed to modify its surface chemical states, including surface plasma treatment, the insertion of metal oxides with a high work function between ITO and organic material, and the formation of a metal-doped indium tin oxide layer on an ITO surface. [6][7][8] Rhodium oxide ͑RhO x ͒ is a transparent conducting oxide. The work function of RhO x ͑ϳ5.0 eV͒ is higher than that of ITO ͑ϳ4.7 eV͒.…”
mentioning
confidence: 99%